INNOVATIVE METHODS IN FORMING STUDENTS' CREATIVE ABILITY (Universal International Scientific Journal, 2026)
This article scientifically analyzes the current issues of developing creativity in students of secondary educational institutions and the pedagogical factors influencing it. Unlike the traditional, solely memorizing education system, the didactic possibilities of innovative approaches that awaken originality in student thinking, in particular, STEAM education, project-based learning (PBL) and design thinking (Design Thinking) methods, are studied. During the study, international best practices in the formation of divergent thinking in students were analyzed and ways of integrating them into national educational practice were shown using examples. The conclusions obtained confirm that the systematic introduction of modern interactive methods into the educational process will dramatically increase not only the students' mastery rate, but also their ability to make independent and non-standard decisions in uncertain situations in the future.
Keywords: creativity; innovative education; creative thinking